2004
DOI: 10.1002/ajhb.20015
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to maternal diabetes is associated with altered fetal growth patterns: A hypothesis regarding metabolic allocation to growth under hyperglycemic‐hypoxemic conditions

Abstract: The prevalence of diabetes is rising worldwide, including women who grew poorly in early life, presenting intergenerational health problems for their offspring. It is well documented that fetuses exposed to maternal diabetes during pregnancy experience both macrosomia and poor growth outcomes in birth size. Less is known about the in utero growth patterns that precede these risk factor expressions. Fetal growth patterns and the effects of clinical class and glycemic control were investigated in 37 diabetic pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 224 publications
(180 reference statements)
1
42
1
2
Order By: Relevance
“…Quando o Diabetes mellitus está presente desde o início da gravidez, estados hiperglicêmicos no primeiro e no segundo trimestre promovem alterações na programação da placenta com alterações no perfil das proteínas transportadoras de glicose (GLUTs), que passam a se expressar de forma diversa nessas placentas. 23,24 Dessa forma, qualquer elevação nos níveis glicêmicos dessas gestantes, no terceiro trimestre, favorece maior transporte da glicose para a circulação fetal. Isso pode facilitar a manutenção do estado de maior produção do líquido amniótico e promover maior crescimento fetal.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Quando o Diabetes mellitus está presente desde o início da gravidez, estados hiperglicêmicos no primeiro e no segundo trimestre promovem alterações na programação da placenta com alterações no perfil das proteínas transportadoras de glicose (GLUTs), que passam a se expressar de forma diversa nessas placentas. 23,24 Dessa forma, qualquer elevação nos níveis glicêmicos dessas gestantes, no terceiro trimestre, favorece maior transporte da glicose para a circulação fetal. Isso pode facilitar a manutenção do estado de maior produção do líquido amniótico e promover maior crescimento fetal.…”
Section: Resultsunclassified
“…25,26,27 Com isso não se constata redução significativa do volume de líquido, mesmo que se obtenha estrito controle no perfil glicêmico. Torna-se importante monitorar o aumento excessivo do volume de líquido, uma vez que a mudança do status quo é que poderá acrescentar risco significativo de descontrole da homeostase materna e/ou fetal 24 . O estudo da placenta de gestantes portadoras de diabetes demonstra que, no termo, a morfologia vilosa é diferente.…”
Section: Resultsunclassified
“…However, gestational diabetes cause greater insulin resistance (Setji, Brown, & Feinglos, 2005), which leads to increase levels of glucose transported across the placenta to the fetus and cause fetal hyperglycemia (Lampl & Jeanty, 2004). The reduced body weight fetuses in STZinduced diabetic group may be due to fetal hypoinsulinemia which causes the growth restriction in fetuses (Aerts & Van Assche, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Lampl et al [32] reported a relatively shorter tibia compared to the thigh, and lower limb relative to upper limb length, among maternal smoke-exposed mid-gestation foetuses, while Lindsay et al [33] reported that tibia and forearm lengths, and especially thigh length, showed greater differences between control and maternal smoke-exposed neonates than total crown-rump length. In relation to diabetes, Lampl et al [34] found stronger effects in the lower limb than the upper limb and in the tibia than the femur, while Catalano et al [12] reported that upper arm, lower arm and lower leg lengths, but not crown-rump or thigh lengths, were significantly smaller in diabetes-exposed neonates, though differences were modest. However, broader trends in these characteristics relative to birth weight are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[16][23]) and postnatal limb proportions may be particularly sensitive to environmental stressors [24][31]. Studies investigating the effects of specific stressors on neonatal development (maternal smoking [32][33] or diabetes [12], [34]) suggest that neonatal trunk, limb and limb segment lengths and proportions are indeed differentially affected. Lampl et al [32] reported a relatively shorter tibia compared to the thigh, and lower limb relative to upper limb length, among maternal smoke-exposed mid-gestation foetuses, while Lindsay et al [33] reported that tibia and forearm lengths, and especially thigh length, showed greater differences between control and maternal smoke-exposed neonates than total crown-rump length.…”
Section: Introductionmentioning
confidence: 99%